Do different habits affect microplastics contents in organisms? A trait-based analysis on salt marsh species. (April 2020) - Piarulli, Stefania; Vanhove, Brecht; Comandini, Paolo; Scapinello, Sara; Moens, Tom; Vrielinck, Henk; Sciutto, Giorgia; Prati, Silvia; Mazzeo, Rocco; Booth, Andy M.; Van Colen, Carl; Airoldi, Laura
Abstract: Salt marshes in urban watersheds are prone to microplastics (MP) pollution due to their hydrological characteristics and exposure to urban runoff, but little is known about MP distributions in species from these habitats. In the current study, MP occurrence was determined in six benthic invertebrate species from salt marshes along the North Adriatic lagoons (Italy) and the Schelde estuary (Netherlands). The species represented different feeding modes and sediment localisation. 96% of the analysed specimens (330) did not contain any MP, which was consistent across different regions and sites. Suspension and facultative deposit-feeding bivalves exhibited a lower MP occurrence (0.5–3%) relative to omnivores (95%) but contained a much more variable distribution of MP sizes, shapes and polymers. The study provides indications that MP physicochemical properties and species' ecological traits could all influence MP exposure, uptake and retention in benthic organisms inhabiting European salt marsh ecosystems. Graphical abstract: Unlabelled Image Highlights: Quantification of microplastics in wild benthic invertebrates from European salt marshes Species with different ecological traits were collected. The 96% of the analysed specimens did not contain any MP. Omnivores contained higher quantities of microplastics than suspension and deposit feeders. Suspension and deposit-feeders exhibited greater variability of MP typologies than omnivores.